The multiarm optimization of stroke thrombolysis phase 3 acute stroke randomized clinical trial: Rationale and methods. Issue 7 (October 2021) - Deeds, S Iris; Barreto, Andrew; Elm, Jordan; Derdeyn, Colin P; Berry, Scott; Khatri, Pooja; Moy, Claudia; Janis, Scott; Broderick, Joseph; Grotta, James; Adeoye, Opeolu
Background: Intravenous recombinant tissue plasminogen activator is the only proven effective medication for the treatment of acute ischemic stroke. Two approaches that may augment recombinant tissue plasminogen activator thrombolysis and prevent arterial reocclusion are direct thrombin inhibition with argatroban and inhibition of the glycoprotein 2b/3a receptor with eptifibatide. Aim: The multi-arm optimization of stroke thrombolysis trial aims to determine the safety and efficacy of intravenous therapy with argatroban or eptifibatide as compared with placebo in acute ischemic stroke patients treated with intravenous recombinant tissue plasminogen activator within 3 h of symptom onset. Sample size estimate: A maximum of 1200 randomized subjects to test the superiority of argatroban or eptifibatide to placebo in improving 90-day modified Rankin scores. Methods and design: Multiarm optimization of stroke thrombolysis is a multicenter, multiarm, adaptive, single blind, randomized controlled phase 3 clinical trial conducted within the National Institutes of Health StrokeNet clinical trial network. Patients treated with 0.9 mg/kg intravenous recombinant tissue plasminogen activator within 3 h of stroke symptom onset are randomized to receive intravenous argatroban (100 µg/kg bolus followed by 3 µg/kg/min for 12 h), intravenous eptifibatide (135 µg/kg bolus followed by 0.75 µg/kg/min infusion for 2 h) or IV placebo. Patients may receive endovascular thrombectomy per usual care. Study outcomes: The primary efficacy outcome is improved modified Rankin score assessed at 90 days post-randomization. Discussion: Multiarm optimization of stroke thrombolysis is an innovative and collaborative project that is the culmination of many years of dedicated efforts to improve outcomes for stroke patients.